Electric Field of a Homogeneous Charged Volumetric Hemisphere Over Its Symmetry Axes - Marón, Pablo; del Vigo, Ángel (Kasuari: Physics Education Journal (KPEJ), 2024)
Analytical study of homogeneous charged volumetric hemisphere electric field along its symmetry axes is presented in this article. Solution was obtained by two different ways; on one hand, superposition of finite thickness disks with increasing radius, and, on the other hand, straightforward integration of finite volume elements in cylindrical coordinates. The same result is obtained in both cases. Additionally, a numerical solution based on the electric field created by a random distribution of discrete charges inside the hemisphere was calculated to check the analytical solution. Concordance between the analytical and numerical solutions was found. The interest of this theoretical result at electronics investigation field resides on its utility to determine the capacity of two opposite hemispheres capacitor system.